Incremental Construction as a Circular Economy Instrument in the Production of Cooperative Housing - Fernanda Paes de Barros Gomide; Luís Bragança; Eloy Fassi Casagrande Junior (Urban Science)
The Circular Economy (CE) proposal aims to minimise waste and maximise the use of resources, making it crucial for providing social housing (SH). Incorporating CE principles into SH policies makes it possible to take significant steps towards a more sustainable and equitable future. The cooperative housing movement offers a solution for growing and empowering local communities to actively develop, own, and manage housing. In some cooperative housing projects, there is the opportunity to use the incremental construction process, which offers the flexibility to adapt construction to residents’ changing circumstances and needs over time. This study aims to verify how circular economy principles applied to incremental construction in case studies of cooperative housing can contribute to more sustainable solutions in the SH sector. By conducting a systematic literature review (SLR) of scientific databases, case studies of cooperative housings that intentionally or unintentionally incorporate the incremental construction tool into their foundations were selected. The analysis and discussions in the study highlight real possibilities for incorporating CE principles into cooperative housing models by appropriating the incremental construction tool.